2022
DOI: 10.3389/fpubh.2022.766943
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal and Neonatal Outcomes in Immigrants From Conflict-Zone Countries: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: ObjectivesThere are controversies regarding the risk of adverse pregnancy outcomes among immigrants from conflict-zone countries. This systematic review and meta-analysis aimed to investigate the risk of perinatal and neonatal outcomes among immigrants from conflict-zone countries compared to native-origin women in host countries.MethodsA systematic search on the databases of PubMed/MEDLINE, Scopus, and Web of Science was carried out to retrieve studies on perinatal and neonatal outcomes among immigrants from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 71 publications
3
20
0
Order By: Relevance
“…Some studies reported that the perinatal health of immigrants were equal or better compared to the native origin population. In contrast, some studies showed that the risk of adverse pregnancy outcomes were poorer than women in the host country [ 6 7 8 9 10 11 ]. Given the lack of conclusive evidence, the aim of this systematic review and meta-analysis was to investigate the risk of adverse maternal and neonatal outcomes in immigrant women compared to native-origin women in the host country.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that the perinatal health of immigrants were equal or better compared to the native origin population. In contrast, some studies showed that the risk of adverse pregnancy outcomes were poorer than women in the host country [ 6 7 8 9 10 11 ]. Given the lack of conclusive evidence, the aim of this systematic review and meta-analysis was to investigate the risk of adverse maternal and neonatal outcomes in immigrant women compared to native-origin women in the host country.…”
Section: Introductionmentioning
confidence: 99%
“…Among adult women, pregnancy, childbirth and the puerperium were the most common major causes of hospitalization both before and after the official outbreak of the war. Immigrant women from the conflict zones were at a higher risk of neonatal mortality and morbidity [ 19 ]. A certain link was observed between the infections of women’s reproductive tracts related to healthcare and a miscarriage history [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These women have medical problems such as infectious diseases or female genital mutilation leading to complications for themselves and their newborns [ 60 – 62 ]. Immigrant women have a poor access to maternity and public healthcare services in host countries [ 63 65 ], which can increase the risk of mortality among their newborns due to maternal disorders, unintended pregnancy, grand multiparity and teenage pregnancies [ 66 , 67 ], preterm birth [ 68 , 69 ], and undiagnosed congenital fetal anomalies [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%